Social Media and Digital Dissidence in Zimbabwe - Matsilele, Trust. author. aut Link
XIX, 165 p.
Keywords: “Trust Matsilele’s Social Media and Digital Dissidence in Zimbabwe offers a highly recommended, complex and original genealogy of dissidence, situating it in the longue durée of representations of dissidence – ranging from folklore to political discourse. For Matsilele, dissidence is principally about restoring hunhu or humanity. Moving beyond the technological determinism of naïve celebrations of social media’s onslaught on the postcolonial state, this book provides a nuanced and deeply contextualized account of how social media shapes and is shaped by histories of dissidence.” — Wendy Willems, Associate Professor in the Department of Media and Communications, London School of Economics and Political Science, UK This book proposes a new theorisation when studying cyber dissidents in an African digital sphere. It argues that social media dissidents are a recent development in a long lineage of dissidents in African societies. Using Zimbabwe as a case study, the study locates contemporary dissidents in the same family with other historical dissident figures found in African orature, the Chimurenga wars, through music, poetry and other forms of expression. The book argues against techno-deterministic approaches to studying social media-born digital dissidence in Africa. It is aimed at scholars dedicated to studying social media movements in African contexts and the global south generally, prompting them to re-evaluate their earlier conclusions and adopt a more nuanced and contextspecific approach. Dr Trust Matsilele is Senior Lecturer in the Media and Public Relations department at Cape Peninsula University of Technology, South Africa, and a fellow of CPUT’s Centre for Communication Studies. He has published extensively in peer reviewed edited books and journals. His research cuts across disciplines such as social media, protest cultures, journalism and education. He is also a former senior journalist with Forbes Africa magazine and CNBC Africa and is regularly featured as a political analyst and social commentator in the media.